PENGARUH KOMPETENSI DAN MASA KERJA TERHADAP PRODUKTIVITAS KERJAKARYAWANPADA PT ALFA RETAILINDO DI MAKASSAR - Zainal Abidin (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
This study aims to Influence Competence and Work Period on Employee Productivity at PT Alfa Retailindo in Makassar. The research method is survey. The population in this research is all employees at PT Alfa Retailindo in Makassar which amounted to 95 people. Because the population is small, the entire population is used as a sample (saturated sample). Techniques of collecting data through questionnaires, interviews, and documentation as a support. Technique of data analysis is doubled linear regression to know influence of independent variable to dependent variable. The result of the research shows that the competence and working period have positive and significant influence both partially and simultaneously to work productivity at PT Alfa Retailindo in Makassar with very strong correlation. This is indicated by the coefficient of determination (R2) of 0.959 (95.9 percent).